(untitled) (Raparin Journal of Humanities (RJH), 2026)
This research is a morphometric analysis of the watersheds in the northern and northeastern valleys of Choman district, which includes several watersheds: Darband, Nawanda, Dilza, and Warda watersheds, with a total area of (83.145) km², located between the latitudes (36°47’10” - 36°47’58”) North and longitudes (44°49’15” - 44°58’46”) East. The highest peak is in Darband watershed at (3607)m, followed by Nawanda watershed at (3584)m, Warda watershed at (2117)m, and Dilza watershed at (2800)m. The lowest points of the watersheds are 1207, 1156, 1137, and 1100 respectively. The length of Darband watershed is (13.65)km, Nawanda watershed (11.99)km, and Dilza watershed (8.63)km. The shortest watershed is Warda at (3.91)km. Darband watershed has the greatest width at (5.67)km, Nawanda (3.26)km, Dilza watershed (2.34)km, and Warda watershed (0.78)km. The drainage density of Darband watershed is (5.47)km²/km, Nawanda watershed (0.48)km²/km, Dilza (0.44)km²/km, and Warda watershed (0.41)km²/km. Generally, all watersheds are close to circular in shape. Detailed morphometric analysis of the watersheds reveals that the morphometry of drainage networks has an impact on the geomorphology and landforms, as well as the size and characteristics of the temporary river systems in the study area. This research utilized remote sensing technology and Geographic Informatio System (GIS) with Digital Elevation Model (DEM) data.